Porokeratosis ptychotropica - Ana Carolina Franco Tebet; Tatiana Gandolfi de Oliveira; Anna Rita Ferrante Mitidieri de Oliveira; Fabiolla Sih Moriya; Jayme de Oliveira Filho; Luiz Carlos Cucé (Sociedade Brasileira de Dermatologia, 2016)
Abstract Porokeratosis is a skin disorder clinically characterized by annular plaques with keratotic borders resembling the Great Wall of China and histopathologically by cornoid lamellae. The disease has several clinical variants. Porokeratosis ptychotropica, which has recently become part of these variants, is quite rare and little known. The entity is characterized by verrucous plaques - which may resemble a psoriasis plaque - that affect the regions of the buttocks, most commonly the gluteal cleft, with or without extremity involvement. Itching is often present. We report a rare case of porokeratosis ptychotropica and highlight its unusual manifestation (single plaque), the first case reported in the Brazilian literature.